Deregulasi Penerbangan dan Kinerja Perusahaan Penerbangan Niaga Berjadwal di Indonesia - Indra Setiawan; Dewi Nusraningrum; Yosi Pahala (Institut Transportasi dan Logistik Trisakti, 2015)
The purpose of this study is to analyze the aviation deregulation and performance of the scheduled commercial airlines. Samples used are domestic flights of 17 companies. Using descriptive analytical research methods. Deregulation encourage the emergence of new low-cost airline. Up to 2012 the share of the domestic passenger market in general is as much as 78% controlled by low-cost airline companies. Garuda Indonesia, which has the operating license to fly as a full service airline only gain a market share of 22%. It is concluded that the trend of domestic passengers as much as 78% are choosing low cost airlines.